Targeted quantification of N-1-(carboxymethyl) valine and N-1-(carboxyethyl) valine peptides of beta-hemoglobin for better diagnostics in diabetes - Jagadeeshaprasad, Mashanipalya G.; Batkulwar, Kedar B.; Meshram, Nishita N.; Tiwari, Shalbha; Korwar, Arvind M.; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (Clinical Proteomics, 2016)
Background: N-1-(Deoxyfructosyl) valine (DFV) beta-hemoglobin (beta-Hb), commonly referred as HbA1c, is widely used diagnostic marker in diabetes, believed to provide glycemic status of preceding 90-120 days. However, the turnover of hemoglobin is about 120 days, the DFV-beta-Hb, an early and reversible glycation product eventually may undergo irreversible advanced glycation modifications such as carboxymethylation or carboxyethylation. Hence quantification of N-1-(carboxymethyl) valine (CMV) and N-1-(carboxyethyl) valine (CEV) peptides of beta-Hb would be useful in assessing actual glycemic status. Results: Fragment ion library for synthetically glycated peptides of hemoglobin was generated by using high resolution-accurate mass spectrometry (HR/AM). Using parallel reaction monitoring, deoxyfructosylated, carboxymethylated and carboxyethylated peptides of hemoglobin were quantified in clinical samples from healthy control, pre-diabetes, diabetes and poorly controlled diabetes. For the first time, we report N-1-beta-valine undergoes carboxyethylation and mass spectrometric quantification of CMV and CEV peptides of beta-hemoglobin. Carboxymethylation was found to be the most abundant modification of N-1-beta-valine. Both CMV-beta-Hb and CEV-beta-Hb peptides showed better correlation with severity of diabetes in terms of fasting glucose, postprandial glucose and microalbuminuria. Conclusions: This study reports carboxymethylation as a predominant modification of N-1-beta-valine of Hb, and quantification of CMV-beta-Hb and CEV-beta-Hb could be useful parameter for assessing the severity of diabetes.
Keywords: Diabetes; Diagnosis; Glycation; Glycemic control; HbA1c; Mass spectrometry

Assessing therapeutic potential of molecules: molecular property diagnostic suite for tuberculosis - Gaur, A. S.; Bhardwaj, A.; Sharma, A.; John, L.; Vivek, M. R.; Tripathi, N.; Bharatam, P. V.; Kumar, R.; Janardhan, S.; Mori, A.; Banerji, A.; Lynn, A. M.; et al. (Journal of Chemical Sciences, 2017)
Abstract: Molecular Property Diagnostic Suite (MPDS TB) is a web tool (http://mpds.osdd.net) designed to assist the in silico drug discovery attempts towards Mycobacterium tuberculosis (Mtb). MPDS TB tool has nine modules which are classified into data library (1–3), data processing (4–5) and data analysis (6–9). Module 1 is a repository of literature and related information available on the Mtb. Module 2 deals with the protein target analysis of the chosen disease area. Module 3 is the compound library consisting of 110.31 million unique molecules generated from public domain databases and custom designed search tools. Module 4 contains tools for chemical file format conversions and 2D to 3D coordinate conversions. Module 5 helps in calculating the molecular descriptors. Module 6 specifically handles QSAR model development tools using descriptors generated in the Module 5. Module 7 integrates the AutoDock Vina algorithm for docking, while module 8 provides screening filters. Module 9 provides the necessary visualization tools for both small and large molecules. The workflow-based open source web portal, MPDS TB 1.0.1 can be a potential enabler for scientists engaged in drug discovery in general and in anti-TB research in particular. Graphical Abstract: SYNOPSIS: A web-based MPDS TB Galaxy tool is developed for assessing therapeutic potential of molecules. MPDS TB is categorized into Data Library, Data Processing and Data Analysis. It can be a potential enabler for scientists engaged in drug discovery in general and in anti-TB research in particular. [Figure not available: see fulltext.] © 2017, Indian Academy of Sciences.
Keywords: chemical analysis; Chemoinformatics; computational chemistry; Diagnosis; Drug discovery portal; Information analysis; Libraries; Molecular graphics; Molecules; Neglected diseases; Open science; Portals; tuberculosis; Web-based technology; Websites

Mitochondrial cytochrome oxidase C subunit III (cox3) gene as a sensitive and specific target for molecular detection of Babesia gibsoni infection in dogs - Betgiri, Aishwarya A.; Jadhav, Sameer N.; Pawde, Mrunalini; Shukla, Anurag; Mote, Chandrashekhar; Pawar, Prashant D.; Shanmugam, Dhanasekaran; Kundu, Krishnendu (Experimental Parasitology, 2019)
A PCR targeting mitochondrial cytochrome oxidase subunit III (cox3) for molecular detection of Babesia gibsoni infection in dogs has been developed in this study. Fifty blood samples from suspected clinical cases from dogs, brought to the veterinary college clinics, were examined for presence of B. gibsoni using conventional diagnosis by microscopic examination of Giemsa stained thin blood smears. In addition, species specific PCRs targeting ITS-1 region (BgITS-1 PCR) and nested PCR targeting 18S ribosomal RNA gene (Bg18SnPCR) were carried out. A 634 bp PCR fragment of B. gibsoni cox3 gene was amplified in positive samples from three geographical locations of Satara, Wai and Pune in Maharashtra state of India. From analysis of the sequence of the B. gibsoni cox3 gene, we found that the Indian isolate had 96-98% similarity to the isolate from Japan and China. Post sequencing, de-novo diagnostic primer pair for species specific amplification of 164 bp fragment of B. gibsoni cox3 was designed and the PCR was standardized. The diagnostic results of de-novo Bgcox3 PCR were compared with BgITS-1 PCR and Bg18S nPCR. Thin blood smears detected 22% (11/50) samples positive for small form of Babesia species. The BgITS-1 PCR detected 25% samples (15/50) as positive and Bg18S nPCR detected 80% (40/50) B. gibsoni positive samples. The de-novo Bgcox3 PCR detected 66% (33/50) samples positive for B. gibsoni (at 95% CI). The analytical sensitivity of cox3 PCR was evaluated as 0.000003% parasitaemia or 09 parasites in 100 mu l of blood. The de-novo diagnostic cox3 PCR did not cross react with control positive DNA from other haemoprotozoa and rickettsia like B. vogeli, Hepatozoon canis, Trypanosoma evansi, Ehrlichia cants and Anaplasma platys. Statistically, cox3 PCR had better diagnostic efficiency than ITS-1 PCR in terms of sensitivity (p = 0.0006). No statistically significant difference between results of cox3 PCR and 18S nPCR was observed (p = 0.1760). Kappa values estimated for each test pair showed fair to moderate agreement between the observations. Specificity of Bgcox3 PCR was 100% when compared with microscopy or BgITS-1 PCR. Sensitivity of Bgcox3 PCR was 100% when compared with that of Bg18S nPCR.
Keywords: Babesia gibsoni; cox3; Diagnosis; Dog; mitochondria; molecular